The Model of Web 2.0 Technologies Implementation in Student’s Self-Development Work - G. D. Bukharova; A. V. Kozlova (Образование и наука)
The paper is devoted to substantiation and development of the model of the web 2.0-technologies implementation in organizing student’s self-dependent work in the course of studying the disciplines based on using the information communications technologies (ICT) in professional activities. The methods applied in the above model development include investigation and analysis of psycho-pedagogical and scientific method materials concerning the research subject; systematization and synthesis of the related data; model development of organizing student’s self-dependent work by using the web 2.0-technologies. The theoretical methodological bases combine the technologies and modeling methods of educational process (P. I. Pidkasistyi, V. A. Slastenin); the theory and methods of organizing student’s independent work (P. I. Pidkasistyi, S. I. Archangelskiy) ; aspects of using web 2.0-technologies in education (E. D. Patarakin, Tim O’Reilly). The paper provides the description of the designed model along with the complex pedagogic conditions for its implementation. The recommendations given by the authors can facilitate development of organizational process of student’s self- dependent work in training for using ICT in professional activities.